Entrepreneurship : Envt Patremony ™ / Nur Azreen Nik Ali, Azimah Ahmad Tarmizi & Nurul Akhmar Zainal - Nik Ali, Nur Azreen; Ahmad Tarmizi, Azimah; Zainal, Nurul Akhmar (2009)
Our company name is Envy Patrimony and it based on providing product. The product that we sell is the one and only the traditional food which is “Telur Pindang”. Our product basically famous among ths Malays and Chinese people. We sell our product for wedding ceremony, restaurant, food stall and others events that suiteble. Not to forget, our company focuses on family oriented that is focus on attracting all member of family to spend their good quality of time together while enjoying eating our product. We choose to use the name “Envy Patrimony” is because the word itself reflect to our continuous heritage by our great grandparents recipe that being envy and admired by people.